Новый способ синтеза 1-арил(гетерил)-2,4-дизамещенных имидазол-5-онов - В. О. Топузян; М. М. Kазaнджян; А. А. Оганесян (ՀՀ ԳԱԱ հրատ.)
Предложен метод синтеза 1-арил(гетерил)-2,4-дизамещенных имидазол-5-онов взаимодействием амидов N-замещенных α,β -дегидроаминокислот с 1,1,1,3,3,3-гексаметилдисилазаном. Փոփոխելով ռեակցիայի պայմանները (ժամանակը, ռեագենտների հարաբերությունը) ուսումնասիրված է N-տեղակալված α,β-դեհիդրաամինաթթուների արիլ- կամ հետերիլ-ամիդների ցիկլման հնարավորությունը 1,1,1,3,3,3-հեքսամեթիլդիսիլազանի օգնությամբ: Ստացված արդյունքները հիմք են տալիս եզրակացնելու, որ 1-արիլ(հետերիլ)իմիդազոլ-5-ոնների սինթեզի համար առաջարկվող եղանակը, ինչպես ժամանակի, այնպես էլ ելքերի տեսակետից, գերազանցում է գրականության մեջ նկարագրվածները: The possibility of the synthesis of 1-aryl(heteryl)-2,4-disubstituted imidazol-5-ones by the interaction of the corresponding amides of N-substituted α,β-dehydroaminoacids with HMDS has been investigated. By varying the reaction conditions (time, reagents ratio) it was determined that in the DMF medium the target products could be synthesized in good yields (60-90 %) with the use of 2 or 3 equivalents of HMDS excess. Based on the latest data it is possible to conclude that the proposed procedure of imidazol-5-ones synthesis exceeds the ones described in literature from the point of view of both the reaction procedure and yields of the target products.
Keywords: Organic Chemistry